Hyperthyroidism with Peritoneal Serositis Leading to Small Bowel Obstruction: A Case Report - Ali Al Sharqi; Ruqaiya Al Shehhi; Miaad Al Hinai; Safiya Al Masrouri; Hani Al Qadhi (Oman Medical Journal, 2025)
Cases of small bowel obstruction in the virgin abdomen are rare and can pose diagnostic challenges, especially when associated with endocrinopathy. We present a young woman with uncontrolled Graves’ disease who was admitted with a small bowel obstruction in a virgin abdomen a few weeks after developing a thyroid storm.